PERBEDAAN STATUS GIZI ANAK USIA 6-24 BULAN ANTARA IBU BEKERJA DAN IBU TIDAK BEKERJA DI DESA PEPEDAN KECAMATAN KARANGMONCOL KABUPATEN PURBALINGGA - Adiratna Sekarsiwi (Universitas Harapan Bangsa Purwokerto, 2013)
Status of work is an attempt to change a person's income so that the needs are met. Inwomen who have a high activity or low income mothers so that mothers can not allocateincome to meet the nutritional intake of children aged 6-24 months with the well so that itcan predispose a mother who has good knowledge but has stunting. The purpose of this study was to determine differences in the nutritional status ofchildren aged 6-24 months between working mothers and the mother does not work. Theresearch method uses analytic observation with a sampling technique is simple randomsampling conducted by cross sectional. Number samples are 71 respondents. How is thedata collection observation and interviews. Data analysis used contingency correlation coefficient t. Results of researchmengggunakan contingency coefficient t which shows the difference nutritional status ofchildren aged 6-24 months with working mothers and Differences nutritional status ofchildren aged 6-24 months with the mother does not work. based on the level ofsignificance (approx. Sig.) 0237 values obtained over the criteria of significance of 0.05.Based on the results of the analysis, it is deduced that the relationship between the twovariables no significance or no difference in the nutritional status of children 6-24 monthsbetween working mothers and mothers do not work Keywords: Nutritional Status, Toddler, Mother's Employment Status